Turkey's July 15th Coup : What Happened and Why - Balci, Bayram; Yavuz, M. Hakan (Book collections on Project MUSE., 2017)
"On July 15, 2016, a faction of the Turkish military tried to overthrow the government of President Recep Tayyip Erdoğan. The attempt failed. The Turkish government blamed the attempted coup on Gülenists, followers of an Islamist movement led by Fethullah Gülen, who had helped Erdoğan and his AK Party get elected and bring an ostensibly 'soft' version of Islam into the secular Turkish government. In alliance with the AK Party, Gülenists over time became widely represented in various government institutions, including the military and police. This volume focuses on the Gülen Movement and its possible role in the failed coup, providing historical and sociopolitical context for what may have led to this conflict. Editors Yavuz and Balcı were among the first to study the movement from its beginning. They and other contributors have spent time in Turkey, Central Asia, and the Balkans examining various dimensions of Gülenist activity as the movement became a major economic and educational force in Turkey and elsewhere. Startled by the 2016 coup attempt, a group of scholars who had studied the Gülenists came together to discuss how and why the once-restrained movement became belligerent opponents of Erdoğan's government. This book is a product of their exchanges and it addresses questions such as: what did researchers fail to see in their earlier studies and how will this major disruption in Turkey affect the future of the movement?"--Provided by publisher.